First dinosaur (Ornithopoda) from Early Cretaceous (Albian) of Oregon, U.S.A. Issue 4 (4th July 2018) - Retallack, Gregory J.; Theodor, Jessica M.; Davis, Edward B.; Hopkins, Samantha S. B.; Barrett, Paul Z.
Abstract : SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Retallack, G. J., J. M. Theodor, E. B. Davis, S. S. B. Hopkins, and P. Z. Barrett. 2018. First dinosaur (Ornithopoda) from Early Cretaceous (Albian) of Oregon, U.S.A. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2018.1486847.